Intertextual Representation of the Orang Asli in the Malaysian Online News Media: A Critical Discourse Analysis (International Journal of Language, Literacy and Translation, 2025)
In media discourse, intertextuality is an important aspect which is concerned with how voices are represented and weaved into news articles. The study sets out to explore how the Orang Asli are intertextually represented in the selected Malaysian news media, namely The Star (mainstream news media) and Malaysiakini (alternative news media). The corpus of this study comprises 24 online news articles from The Star (n=12) and Malaysiakini (n=12), respectively. The analysis is grounded on Fairclough’s (1995b) Three-Dimensional Critical Discourse Analysis (CDA) Framework focusing on the intertextual aspect, notably the news articles' discourse representation. The results showed that the voices of the authorities were represented more frequently in The Star as compared to the Orang Asli, whereas both voices were represented fairly by Malaysiakini. Furthermore, the quotation patterns revealed that the authorities were directly quoted more frequently than the Orang Asli, especially in The Star. Although Malaysiakini quoted the Orang Asli, the quotations continue to perpetuate an inferior and stereotypical imagery of the community which revolves around vulnerable and dependent narratives. In general, the intertextual analysis reveals that the authorities’ voices continue to predominate the mainstream media in reinforcing existing perceptions of the Orang Asli community as well as speaking on behalf of the community, which in turn suppresses the Orang Asli’s voices.